PENGARUH HUBUNGAN KERJA, MOTIVASI KERJA, DAN LINGKUNGAN KERJA TERHADAP PRESTASI KERJA KARYAWAN - Sutarno, Atik Dwi Pratiwi, Amin Wahyudi & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2016)
This research aims to influence the employment of employee performance, the effect of work motivation on employee performance, the effect of the work environment on employee performance, and which variables that have a dominant influence on employee performance. The population in this study were all employees of PT Guwatirta Prosperous Karanganyar many as 40 people. Data collection techniques using questionnaires and documentation. Data were analyzed using multiple linear regression analysis. The results of this study showed that there are significant positive working relationship on employee performance, there are positive influence work motivation on employee performance, there is a positive influence on the work environment on employee performance and work motivation is the variable most dominant employee performance. Advised companies can improve working relationships and motivate employees well and be able to create a work environment that is comfortable and safe. Keywords: work relationship, work motivation, work environment, performance.